Analysis Of Tourism Stakeholders’ Willingness To Pay For Environmental Conservation: A Case Study Of Pulau Weh Nature Tourism Park - Amanda Ridwan; Aliasuddin Aliasuddin; Farhan Ramadhani (AJIRSS: Asian Journal of Innovative Research in Social Science, 2026)
This study examines the willingness to pay among tourism operators for environmental conservation within Pulau Weh Nature Tourism Park and delineates the factors influencing this willingness. A quantitative methodology was employed, utilizing structured interviews via questionnaires administered to 48 tourism operators, including tour guides, dive operators, hotel and guesthouse proprietors, as well as restaurant and café owners in Iboih Village. Stratified random sampling was employed to select participants from a population of 148 tourism operators.